Accuracy of determination of longitudinal coordinates of particles by digital holography - Dyomin, Victor V.; Davydova, Alexandra Yu; Polovtsev, Igor G.; Yudin, Nikolay N.; Zinoviev, Mikhail M. (Atmospheric and oceanic optics)
Based on known expressions applied to diffraction-limited optics systems, estimates are given and a technique is suggested for determining the measurement error in the longitudinal coordinates of particles from images reconstructed from digital holograms. A correction factor for visual focusing is determined for different distances between a detected particle and the plane of a CMOS array. The results of experimental tests of the technique are presented. A possibility is shown of reducing the error of automatic digital focusing by means of simultaneous use of focusing curves for several quality indicators and optimization of the image area for their construction